THE IMPORTANCE OF THE MINIMUM WAGE IN INCREASING PRODUCTIVE EMPLOYMENT OF THE POPULATION - Kurbonov Samandar Pulatovich (Labor economics and human capital, 2025)
Productiv employed individuals within the population not only contribute to economic growth but also ensure a level of income sufficient to meet consumption needs for a decent standard of living. This article explores the minimum wage and its key aspects in the context of increasing productive employment, as well as its impact as an indicator of employees’ labor income. It also examines strategies aimed at expanding the scale of productive employment. In this small study, various research works on the role of minimum wage in enhancing productive employment have been analyzed, and the scientific approaches used in them have been systematized. As a scientific result of the study, recommendations are proposed for increasing the level of productive employment among the country’s population.